THE IMPACT OF PRICE POLICY SUPPORT ON INDONESIAN CASSAVA FARMERS - Muhamad Emil Rachman; Muhammad Nursan (Fakultas Pertanian Universitas Mataram, 2023)
Cassava is a carbohydrate-producing plant that can replace other crops such as rice and corn which are widely consumed by the community. The price policy of cassava farmers in the last five years has decreased very significantly, so it is necessary to conduct research on the impact of policies issued by the government. Factors in producing cassava also need to be improved, one of which is increasing productivity through fertilizer subsidies so that the output produced is positive from upstream to downstream, especially in the economy of Indonesian cassava farmers. This study aims to see the impact of the price policy of cassava farmers and production supporting factors in the form of fertilizer subsidy policies so that farmers' welfare levels. This study uses data from 2000 to 2019, the simultaneous equation model consists of 20 equations which are estimated using the Two Stage Least Square (2SLS) method.